2022
DOI: 10.1111/infa.12485
|View full text |Cite
|
Sign up to set email alerts
|

Infants preferentially learn from surprising teachers

Abstract: Infants have sophisticated knowledge about the physical world, and show enhanced learning about objects that violate physical principles. However, it is unknown whether infants also preferentially learn from the individual who produces an outcome that violates expectations. We investigated whether 15-month-old infants (N = 48) selectively imitate individuals who produce surprising outcomes. In Experiment 1, infants watched an experimenter hide a ball and produce an expected outcome in which the ball was reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Strong evidence for the construct validity of the VOE method comes from a newly emerging line of research that examines the functional utility of infants' behaviours following violations of expectation. When infants witness unexpected events, they are more likely to engage in targeted learning and exploration (e.g., Perez & Feigenson, 2022; Sim & Xu, 2017; Stahl & Feigenson, 2015; Stahl & Woods, in press; see Stahl & Feigenson, 2019 for review). Stahl and Feigenson (2015) presented infants with VOE events involving physical violations that typically elicit longer looking (e.g., a rolling car appeared to pass through a wall in its path), and found that infants more effectively learned novel information about objects that violated their expectations than objects that accorded with their expectations.…”
Section: The Voe Methods Yields Consistent Results Across Dependent M...mentioning
confidence: 99%
“…Strong evidence for the construct validity of the VOE method comes from a newly emerging line of research that examines the functional utility of infants' behaviours following violations of expectation. When infants witness unexpected events, they are more likely to engage in targeted learning and exploration (e.g., Perez & Feigenson, 2022; Sim & Xu, 2017; Stahl & Feigenson, 2015; Stahl & Woods, in press; see Stahl & Feigenson, 2019 for review). Stahl and Feigenson (2015) presented infants with VOE events involving physical violations that typically elicit longer looking (e.g., a rolling car appeared to pass through a wall in its path), and found that infants more effectively learned novel information about objects that violated their expectations than objects that accorded with their expectations.…”
Section: The Voe Methods Yields Consistent Results Across Dependent M...mentioning
confidence: 99%
“…We know less, however, about the principles that guide how children explore. Children might explore to minimize surprising events (Ronfard et al, 2021;Stahl & Feigenson, 2017;Stahl & Woods, 2022), where surprise originates from a mismatch between their expectations (i.e., predictions) about the world and the reality of a situation. For example, infants might expect that objects fall to the ground when dropped.…”
Section: Introductionmentioning
confidence: 99%